Propuesta de reingeniería de procesos administrativos para la Empresa Seprytsa S.A. - Monga Sánchez, Mercedes Belén (2018)
The present researching: “Proposal of Reengineering of Administrative Processes for the Company Seprytsa S.A.” To demonstrate that reengineering within the organization may be the best alternative to improve and maintain its competitiveness in the market. The investigation was conducted in Latacunga city, Cotopaxi province, where the company is located. The proposed study is presented as a bibliographical investigation and a field modality is adopted, which allowed the evaluation of a current internal situational diagnosis of the organization. By means of the information gathering of the certification, the limitation of functions, lack of processes, professional profiles, work instructions were analyzed, which is affected the progress of the same. Using the investigative tools of survey and interview, it was found that the organization only has empirical documentation. The inductive and deductive method was also used, developing fundamental categories through a SWOT analysis. For this reason a reengineering was proposed in the company Seprytsa S.A. Within the proposal has been a proposed change in operational, strategic and support processes, seeking to create efficient processes. Through the design of a process manual, a model is proposed to establish management indicators that will help monitor and control each process, allowing the creation of an improvement plan between activities and profitability. In addition, it is vital to foster bonds of friendship and work unity, for which the research focuses its attention on the human talent of the company, reflected in job stability and satisfaction in the development of their activities. Finally it is concluded that the functions within the company to be efficient should be viewed as processes, to assess and enhance their contribution to customer satisfaction, strengthening the corporate image.